Monodisc strobilation in Japanese giant box jellyfish Morbakka virulenta (Kishinouye, 1910): a strong implication of phylogenetic similarity between Cubozoa and Scyphozoa. Issue 4 (July 2015) - Toshino, Sho; Miyake, Hiroshi; Ohtsuka, Susumu; Adachi, Aya; Kondo, Yusuke; Okada, Shoma; Hirabayashi, Takeshi; Hiratsuka, Tatsuya
SUMMARY Both sexes of the Japanese giant box jellyfish Morbakka virulenta were collected from the Seto Inland Sea, western Japan in December 2011, in order to observe the developmental processes from polyps to medusae. The medusa production in M. virulenta is up to now a unique process in cubozoans in that it exhibits a form of monodisc strobilation where the polyp is regenerated before the medusa detaches. This mode of medusa production was previously thought to be exclusive to scyphozoans. The general shape of young medusae resembles that of other cubozoans such as Alatina moseri and Copula sivickisi, but is differentiated from these by the short capitate tentacles and the lack of gastric filaments in the stomach. The unique medusa production of M. virulenta highly implies a phylogenetic similarity between cubozoans and scyphozoans.